Evolution of the System of Elections to the Polish Sejm – the Matter of Election Formula - Rachwał, Marcin (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2017)
The subject matter of this article is evolution of the system of elections to the Polish Sejm within period between 1991 and 2015. The conducted research paid particular attention to the election formula, which is the principle for converting votes into mandates (we can distinguish three types of election formulas: proportional, majority and mixed). The research leads to a conclusion that the election formula has been a vital aspect of the political discourse between 1991 and 2015. Considerable support among the citizens of the Republic of Poland for the idea of adopting the majority formula in elections to the Sejm (in place of the proportional representation formula which has been applied since 1991) should be a stimulus for a thorough constitutional debate within the subject concerned because the principles of elections need to enjoy a broad social acceptance. Supporters of the single-mandate constituencies rise an argument that e.g. the said election formula draws the nation and political authorities closer together because position of the parliament members in the constituency becomes more important than his/her position within the managerial circles of the political party (the electoral committee) that develops the electoral registers.

Przedmiotem artykułu jest kwestia ewolucji systemu wyborczego do Sejmu RP w latach 1991– 2015. Szczególne miejsce w podjętych badaniach stanowiła kwestia formuły wyborczej, która oznacza zasadę przekształcania głosów wyborców na mandaty (można wyróżnić trzy formuły wyborcze: proporcjonalną, większościową, mieszaną). Przeprowadzone badania skłaniają do wniosku, iż kwestia formuły wyborczej stanowiła istotny aspekt prowadzonego w latach 1991–2015 dyskursu publicznego. Znaczne poparcie obywateli RP dla idei ustanowienia w wyborach do Sejmu formuły większościowej (w miejsce obowiązującej od 1991 roku formuły proporcjonalnej) powinno być impulsem do podjęcia pogłębionej debaty konstytucyjnej w zasygnalizowanym zakresie przedmiotowym, gdyż same zasady przeprowadzania wyborów powinny cieszyć się szerokim poparciem społecznym. Zwolennicy jednomandatowych okręgów wyborczych przywołują m.in. argument, iż wskazana formuła wyborcza zbliża przedstawicieli do narodu, gdyż ważniejsza staje się pozycja posła w okręgu wyborczym niż w gremiach kierowniczych partii politycznych (komitetów wyborczych) ustalających kształt list wyborczych.
Ewolucja systemu wyborczego do Sejmu RP – kwestia formuły wyborczej
Keywords: Sejm; Sejm; electoral system; system wyborczy; proportional representation; formuła proporcjonalna; majority rule; formuła większościowa; single-mandate constituencies; jednomandatowe okręgi wyborcze Data przekazania